Editorial: Insights in biosafety and biosecurity 2022: Novel developments, current challenges, and future perspectives - Pillai, Segaran P.; Raybould, Alan (Frontiers in Bioengineering and Biotechnology, 2023)
Biosafety and Biosecurity covers the relationship between bioengineering and biotechnology and the assessment and management of risk to human and animal health and the environment. This relationship includes both the risk posed by research and its application and the research and application to reduce risk through bioengineering and biotechnology. To this end, Frontiers developed a Research Topic entitled “Insights in Biosafety and Biosecurity 2021: Novel Developments, Current Challenges, and Future Perspectives” that encompasses human health and environmental risk assessments of bioengineering and biotechnology when used as a tool in basic or applied research. In 2021, 9 manuscripts were originally submitted for this research Topic. Of those 8 (89%) were accepted. To support the safety and security mission it is critical to ensure the protection of workers and prevent work-related injuries, illnesses, and deaths by setting and enforcing standards, and by providing training, outreach, education, and assistance. It is also important to establish policies and practices to ensure that the work is executed safely by employing various controls (engineering and administrative), personal protective equipment, leveraging new biotechnology, performing appropriate hazards identification, risk assessments and implementing risk mitigation strategies.